PREDICTION OF PERSISTENT PERITONITIS IN THE POSTOPERATIVE PERIOD - J.A. ABDULLOZODA; A.R. SARAEV; SH.K. NAZAROV; S.G. ALI-ZADE (Avicenna Tajik State Medical University, 2024)
Objective: Improve the treatment results of patients with diffuse peritonitis by accurately predicting the progression of persistent peritonitis to septic shock in the postoperative period Methods: The study involved 75 patients with diffuse peritonitis. These patients were split into two groups based on whether their peritonitis persisted after surgery and if they needed further surgery. The study used pre- and intraoperative clinical and laboratory predictors to determine the progression of peritonitis to septic shock Results: The preoperative CT attenuation coefficient of intraperitoneal fluid, measured in Hounsfield units (HU), was significantly higher in the study group compared to the control group (28.35 HU vs. 18.3 HU; p<0.001). The scores on the Mannheim Peritonitis Index (MPI) were also significantly higher in the study group compared to the control group (25 versus 16; p<0.001). Additionally, the levels of presepsin (PSEP), procalcitonin (PCT), and C-reactive protein (CRP) were higher in the study group compared to the control group (p<0.001): 1149.1 (153.7-2591) pg/ml, 12.7815 (4.286-22.557) ng/ml, and 232.5 (162.2-312.4) mg/l in the study group, and 410.3 (56.1-980.9) pg/ml, 3.087 (0.995-13.399) ng/ml, and 120.8 (25.7-280) mg/l in the control group, respectively Conclusion: The proposed method for predicting the progression of peritonitis to septic shock is based on the MPI score and the CT attenuation coefficient of intraperitoneal fluid, in combination with biomarkers of inflammation such as PSEP, PCT, and CRP. This method allows practical surgeons to recognize persistent peritonitis, be prepared for the deterioration of a patient's condition with the progression of persistent peritonitis to septic shock, and perform a timely and appropriate surgical intervention